Assistive technology solutions for aiding travel of pedestrians with visual impairment. (August 2017) - Chanana, Piyush; Paul, Rohan; Balakrishnan, M; Rao, PVM
This work systematically reviews the assistive technology solutions for pedestrians with visual impairment and reveals that most of the existing solutions address a specific part of the travel problem. Technology-centered approach with limited focus on the user needs is one of the major concerns in the design of most of the systems. State-of-the-art sensor technology and processing techniques are being used to capture details of the surrounding environment. The real challenge is in conveying this information in a simplified and understandable form especially when the alternate senses of hearing, touch, and smell have much lesser perception bandwidth than that of vision. A lot of systems are at prototyping stages and need to be evaluated and validated by the real users. Conveying the required information promptly through the preferred interface to ensure safety, orientation, and independent mobility is still an unresolved problem. Based on observations and detailed review of available literature, the authors proposed that holistic solutions need to be developed with the close involvement of users from the initial to the final validation stages. Analysis reveals that several factors need serious consideration in the design of such assistive technology solutions.